The influence of kinematic viscosity of oils on the energy consumption of a gear pump used for pumping oil in machines and vehicles - Łukasz Warguła; Łukasz Gierz; Olga Zharkevich; Bartosz Wieczorek; Łukasz Wojciechowski; Karolina Perz; Alexandra Berg; Andrey Berg; Darkhan Zhunuspekov; Asset Altynbaev; Piotr Kaczmarzyk; Anna Dziechciarz (PLoS ONE, 2025)
The general theory of oil pumping using gear pumps shows that as kinematic viscosity increases, so does the energy requirement to drive the pump shaft. However, modern oils used in machines and vehicles are characterized by a wide range of modifiers that alter their physical and chemical properties. This article presents a study on the energy demand for driving a gear pump while pumping commercial oils used in machines and vehicles (16 types), such as those for combustion engines in single-drive and hybrid vehicles, gearboxes, hydraulic systems, shock absorbers, chainsaw lubrication, and two-stroke engine fuel mixtures. For the tested oils, kinematic viscosity was determined at 25°C and 50°C, and the mechanical power required to pump them at an ambient temperature of approximately 25°C was measured. Based on the measured power and rotational speed, the energy demand for driving the gear pump was calculated. The main analysis was conducted under recommended operating conditions, where the pump operates most efficiently—namely, at a rotational speed of 2000 rpm and a pressure of 20 MPa. It was shown that within the tested group, kinematic viscosity is not the primary factor determining the energy intensity of the oil pumping process. However, this relationship becomes more evident when oils are grouped by application. The energy consumption during pumping of oils with kinematic viscosity at 25°C ranging from 21 to 784.5 mm2/s varies from 606 to 734 Wh. The difference due to the type of oil is approximately 21%. The lowest energy consumption was observed for the HL 46 hydraulic oil, which, although not having the lowest kinematic viscosity, was specifically designed by the manufacturer for use with gear pumps—indicating that pump designs are tailored to the specific type of oil being pumped.